ABOUT SOME SIDES OF DIPLOMACY AND POLITICAL COOPERATION OF KAZAKHSTAN WITH THE COUNTRIES OF THE MIDDLE EAST - Ayupova Z. K.; Kussainov D. U.; Nagan Winston (Scientific Journal of Pedagogy and Economics, 2019)
The general characteristic of diplomatic and political cooperation of the Republic of Kazakhstan with the countries of the Middle East is presented in this article. At the present stage the countries of the Middle East have powerful political, business and intellectual potential. In the international system of energy balance of the countries of this region hold a specific place, that allowed them to create the largest financial and economic centers, rendering on geopolitical alignment of forces in the modern world considerable influence. From the moment of independence the Republic of Kazakhstan tried to establish friendship with the countries of the Middle East, showed the intentions to the closest interaction. Kazakhstan defined them as the perspective partners in the economic, political and cultural relations have all necessary prerequisites and conditions for mutual understanding and cooperation. Signing by Astana and Ankara of a package of important interstate agreements contributed to the forward development both diplomatic contacts between two countries, trade and economic relations, including the summits of the Turkicspeaking states. Dynamically developing bilateral relations of Kazakhstan and Turkey found the reflection in joint actions for implementation of the Baku-Tbilisi-Ceyhan project.